The signal of snowmelt in streamflow and stable water isotopes in a high mountain catchment in Central Spain - J.I. López-Moreno; I. Granados; A. Ceballos-Barbancho; E. Morán-Tejeda; J. Revuelto; E. Alonso-González; S. Gascoin; J. Herrero; C. Deschamps-Berger; J. Latron (Journal of Hydrology: Regional Studies, 2023)
Study region: Peñalara catchment, in the mountains of the Central System in Spain, Study focus: For the first time, we investigated the streamflow and streamwater isotopes during the snow accumulation and melting periods and over subsequent months in two snow seasons. The aim is to better understand the hydrological processes linked to snowmelt; to describe the temporal evolution and the interannual differences in isotopic streamwater; and to improve the understanding about the hydrological functioning of snowmelt water across the catchment. New hydrological insights for the region: The isotopic signal of the streamwater progressively became isotopically depleted from the beginning of the melt period until the snow cover depletion of the catchment. Higher snowfall led to depleted isotopic values in the stream compared to a year with low snowfall. The interannual variability of the isotopic signature of streamwater during snowmelt may represent a difficulty to establishing reference values to be used in mixing models for hydrograph separation. The streamflow isotopic values had very limited sub-daily variation and showed slow temporal changes, suggesting a central role for alpine aquifers in explaining the hydrological functioning of the catchment, pointing to piston flow as a key process in streamflow generation.